The Effect of Problem-Based Learning Assisted by Monopoly Game Media on Elementary Students' Numeracy Skills and Learning Interests - Rizky Dwi Pangestika; Gunawan (Universitas Islam Negeri Raden Intan Lampung, 2026)
Numeracy skills and learning interest are central to elementary mathematics learning because they shape students’ ability to interpret quantitative information, solve contextual problems, and sustain meaningful engagement in classroom activities. However, mathematics instruction at the elementary level often remains procedural and insufficiently interactive, limiting students’ willingness to participate in numeracy-based problem solving. This study examined the effect of Problem-Based Learning assisted by monopoly media on Grade VI students’ numeracy skills and learning interest, while also investigating the relationship between both variables. A quantitative quasi-experimental design with a nonequivalent control group was employed. The participants were 50 Grade VI students from two elementary school classes in North Purwokerto, Banyumas, Indonesia, consisting of 25 students in the experimental class and 25 students in the control class. Data were collected using a numeracy skills test, a learning interest observation sheet, and documentation. The data were analyzed through descriptive statistics, Shapiro-Wilk normality testing, Levene’s homogeneity testing, independent samples t-test, effect size analysis, and Pearson correlation. The findings showed that the experimental class achieved higher mean scores than the control class in both numeracy skills and learning interest. The most robust effect was observed in learning interest, supported by a moderate practical effect, indicating that monopoly media functioned as an affective engagement mechanism within the PBL framework. In contrast, the effect on numeracy skills was positive but practically limited, suggesting that cognitive improvement requires longer intervention and stronger instructional scaffolding. A strong positive correlation was also found between numeracy skills and learning interest. This study contributes by positioning monopoly-media-assisted PBL as a pedagogical approach that primarily strengthens affective engagement while providing supportive conditions for sustained numeracy development